Beyond cyanotoxins: increased Legionella, antibiotic resistance genes in western Lake Erie water and disinfection-byproducts in their finished water - Lee, Jiyoung; Lee, Seungjun; Hu, Chenlin; Marion, Jason W. (Frontiers in Microbiology, 2023)
Western Lake Erie is suffering from harmful cyanobacterial blooms, primarily toxic Microcystis spp., affecting the ecosystem, water safety, and the regional economy. Continued bloom occurrence has raised concerns about public health implications. However, there has been no investigation regarding the potential increase of Legionella and antibiotic resistance genes in source water, and disinfection byproducts in municipal treated drinking water caused by these bloom events. Over two years, source water (total n=118) and finished water (total n= 118) samples were collected from drinking water plants situated in western Lake Erie (bloom site) and central Lake Erie (control site). Bloom-related parameters were determined, such as microcystin (MC), toxic Microcystis, total organic carbon, N, and P. Disinfection byproducts (DBPs) (total trihalomethanes (THMs) and haloacetic acids (HAAs)) were assessed in finished water. Genetic markers for Legionella, antibiotic resistance genes, and mobile genetic elements were quantified in source and finished waters. Significantly higher levels of MC-producing Microcystis were observed in the western Lake Erie site compared to the control site. Analysis of DBPs revealed significantly elevated THMs concentrations at the bloom site, while HAAs concentrations remained similar between the two sites. Legionella spp. levels were significantly higher in the bloom site, showing a significant relationship with total cyanobacteria. Abundance of ARGs (tetQ and sul1) and mobile genetic elements (MGEs) were also significantly higher at the bloom site. Although overall abundance decreased in finished water, relative abundance of ARGs and MGE among total bacteria increased after treatment, particularly at the bloom site. The findings underscore the need for ongoing efforts to mitigate bloom frequency and intensity in the lake. Moreover, optimizing water treatment processes during bloom episodes is crucial to maintain water quality. The associations observed between bloom conditions, ARGs, and Legionella, necessitate future investigations into the potential enhancement of antibiotic-resistant bacteria and Legionella spp. due to blooms, both in lake environments and drinking water distribution systems.